Evaluation of the correlation between preoperative airway assessment tests, anthropometric measurements, and endotracheal intubation difficulty in obesity class III patients undergoing bariatric surgery. Issue 36 (10th September 2021) - Emik, Emre; Gümüs-Özcan, Funda; Demirgan, Serdar; Selcan, Aysin
Abstract : Abstract: In this study, we investigated the correlation between airway assessment tests, anthropometric measurements, and the Modified Cormack– Lehane Classification (MCLC) assessed by videolaryngoscopy in patients undergoing bariatric surgery. This study included 121 morbidly obese patients undergoing bariatric surgery. The body mass index, Modified Mallampati Score (MMS), thyromental distance, sternomental distance, interincisor distance, and neck, waist, and chest circumferences were recorded. The correlation between the airway assessment tests, anthropometric parameters, and the MCLC were analyzed. The time required for endotracheal intubation (EI) and the attempt required for EI were also recorded. Thirty-three patients were found to be at risk of a difficult EI. The MMS, neck circumference, waist circumference, chest circumference, the time required for EI, and the number of attempts for EI were positively correlated with MCLC (all P < .05). As the MMS increased, the risk of a difficult EI increased ( P < .001). The cutoff values of neck, waist, and chest circumference for the risk of a difficult EI were 41.5, 153.5, and 147.5 cm, respectively ( P < .05). This study indicates that the high MMS, as well as increased neck, waist, and chest circumference, should be considered EI difficulty in obese patients, even if a videolaryngoscopy is used.